PENGARUH IKLIM ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMP/MTs DI KECAMATAN SUSUKAN KABUPATEN SEMARANG - Dwi Any Wurjayanti; Sudharto Sudharto; Fenny Roshayanti (Jurnal Manajemen Pendidikan (JMP), 2020)
The problems in this study are: (1) is there an influence of organizational climate on the performance of junior / MTs teachers in Susukan District, Semarang Regency; (2) is there any influence of work motivation on the performance of SMP / MTs teachers in Susukan District, Semarang Regency; (3) is there an influence of organizational climate and work motivation on the performance of SMP / MTs teachers in Susukan District, Semarang Regency.The purpose of this study is: (1) to find out whether there is an influence of organizational climate on teacher performance; (2) to find out whether there is an effect of work motivation on teacher performance; (3) to find out whether there is an influence of organizational climate and work motivation on the performance of SMP / MTs teachers in Susukan District, Semarang Regency.The population in this study were SMP / MTs teachers in Susukan District, Semarang Regency, which amounted to 157 people, with a sample of 113 people determined by proportional random sampling technique. Data collection using a questionnaire. The data analysis used was descriptive analysis, requirements test, single regression analysis and multiple regression analysis which was calculated using the SPSS for Windows version 21 program.From the results of the study, it can be seen that the average score of the organizational climate score of 120.58 is quite good; the average work motivation score of 126.16 includes a fairly good category; the average score of the teacher's performance score of 117.30 is quite good. Prerequisite test results from the research data obtained normal distribution data, homogeneous, linear, not multicollinear, and heteroscedasticity did not occur. From the hypothesis test it was found that there was a positive influence of the organizational climate on teacher performance as stated by the equation Y = 68.786 + 0.402X1; correlation strength of 0.405 with a contribution of 0.164 or 16.4%. There is a positive effect of work motivation on teacher performance which is expressed by the equation Y = 69.409 + 0.380X2; correlation strength of 0.389 with a contribution of 0.151 or 15.1%. There is a positive influence of organizational climate and work motivation together on teacher performance which is expressed by the equation Y = 49,624 + 0,290X1 + 0,259X2; with contributions of 0.221 or 22.1%.The performance of junior high school / MTs teachers in Susukan District, Semarang Regency is influenced by the organizational climate and work motivation of teachers. Aspects of warmth, personal relationships between school members, and the task of teachers in terms of training students still need to be improved. The principal must make efforts to improve the condition.